2019
DOI: 10.1186/s13227-019-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms underlying the evolution of form and function in the amniote jaw

Abstract: The amniote jaw complex is a remarkable amalgamation of derivatives from distinct embryonic cell lineages. During development, the cells in these lineages experience concerted movements, migrations, and signaling interactions that take them from their initial origins to their final destinations and imbue their derivatives with aspects of form including their axial orientation, anatomical identity, size, and shape. Perturbations along the way can produce defects and disease, but also generate the variation nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 340 publications
(319 reference statements)
0
23
0
1
Order By: Relevance
“…6D). Humans and rats, but not mice, opposums and guinea pigs, develop a coronoid secondary cartilage 312 . Despite the lack of a coronoid cartilage in mice (Fig.…”
Section: Secondary Cartilage Takes the Leading Rolementioning
confidence: 94%
“…6D). Humans and rats, but not mice, opposums and guinea pigs, develop a coronoid secondary cartilage 312 . Despite the lack of a coronoid cartilage in mice (Fig.…”
Section: Secondary Cartilage Takes the Leading Rolementioning
confidence: 94%
“…While our results indicate that promoter evolution may play an important role in the species-specific expression of Mmp13 and in this way could influence the establishment of jaw length in quail versus duck via bone resorption, the potential contributions from additional levels of Mmp13 regulation, multiple Mmps, as well as different members and targets of TGFβ and other signaling pathways remain vast (Mina, 2001b;Mina, 2001a;Depew et al, 2002;Mina et al, 2002;Chakraborti et al, 2003;Oka et al, 2007;Havens et al, 2008;Balic et al, 2009;Fanjul-Fernandez et al, 2010;Fish et al, 2011;Young et al, 2019). In prior studies we have found that NCM-mediated programs underlying jaw development in quail and duck also vary due to species-specific differences in the cell biological properties of NCM and in the physical and signaling interactions between NCM and adjacent tissues (Schneider and Helms, 2003;Schneider, 2007;Eames and Schneider, 2008;Merrill et al, 2008;Tokita and Schneider, 2009;Solem et al, 2011;Fish and Schneider, 2014b;Fish et al, 2014;Hall et al, 2014;Ealba et al, 2015;Schneider, 2015;Woronowicz et al, 2018;Woronowicz and Schneider, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, as an initial read-out of the patterning road-map of the cephalic ectoderm and the λ-junction we examined the expression patterns of Bmp4 at E10. 25 and Fgf8 at E10.75 ( Figure 10). While we found, as expected, that normal distal mdBA1 Bmp4 expression was robust in double mutant embryos, we also unexpectedly found a near complete loss of junctional Bmp4 expression.…”
Section: Fundamental Re-patterning Of the Sce And Lj Of Foxg1 -/-;Dlxmentioning
confidence: 99%
“…As the vast majority of vertebrates are gnathostomes, and thus possess jaws, the true enormity of the observed radiation and diversification of vertebrates must be regarded in the particular light of the acquisition and modification of jaws . Jaws are prehensile oral apparatuses that can be further defined by their possession of two appositional units -the upper and lower arcades -that are articulated (hinged) and which largely arise during development from the first branchial arch (BA1) (5)(6)(7)(8)(9)(10)(11)(12)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%